Novel regulatory mechanism of serine biosynthesis associated with 3-phosphoglycerate dehydrogenase in Arabidopsis thaliana - Eiji Okamura; Masami Yokota Hirai (Scientific Reports, 2017)
Abstract The proteinogenic amino acid l-serine is a precursor for various essential biomolecules in all organisms. 3-Phosphoglycerate dehydrogenase (PGDH) is the first committed enzyme of the phosphorylated pathway of l-serine biosynthesis, and is regulated by negative feedback from l-serine in bacteria and plants. In the present study, two Arabidopsis PGDH isoforms were inhibited by l-serine but were activated by l-amino acids such as l-homocysteine in vitro. Activation and inhibition by these amino acids was cooperative, suggesting an allosteric mechanism. Moreover, the half maximal effective concentration of l-homocysteine was 2 orders of magnitude lower than that of l-serine, suggesting greater regulatory potency. These are the first data to show that PGDH is activated by various biomolecules and indicate that serine biosynthesis is regulated by multiple pathways.